A novel NIR-image segmentation method for the precise estimation of above-ground biomass in rice crops. - CGIAR Research Program on Rice (2020)
Filed experiments were concluded to provide proof of concept. Accurate plot segmentation results enabled the extraction of several canopy features associated with biomass yield. The software for aerial biomass estimation is available for other users.